2003
DOI: 10.1051/0004-6361:20030240
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar envelope of the C-rich post-AGB star HD 56126

Abstract: Abstract. We present a detailed study of the circumstellar envelope of the post-asymptotic giant branch "21 µm object" HD 56126. We build a detailed dust radiative transfer model of the circumstellar envelope in order to derive the dust composition and mass, and the mass-loss history of the star. To model the emission of the dust we use amorphous carbon, hydrogenated amorphous carbon, magnesium sulfide and titanium carbide. We present a detailed parametrisation of the optical properties of hydrogenated amorpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 76 publications
6
88
0
Order By: Relevance
“…As shown in Figure 3c, the AIBs and aliphatic IR bands are superimposed on two broad plateau features around 8 and 12 µm. The spectral characteristics of LT condensates strongly resemble the observed IR spectra of post AGB stars and protoplanetary nebulae (Kwok et al 2001, Hony et al 2003, Hrivnak et al 2007). The comparison shown in Figure 3c clearly reveals that nearly all of the observed IR bands are also present in the LT condensate produced in the laboratory.…”
Section: Spectral Properties Of the Ht And Lt Condensatessupporting
confidence: 57%
“…As shown in Figure 3c, the AIBs and aliphatic IR bands are superimposed on two broad plateau features around 8 and 12 µm. The spectral characteristics of LT condensates strongly resemble the observed IR spectra of post AGB stars and protoplanetary nebulae (Kwok et al 2001, Hony et al 2003, Hrivnak et al 2007). The comparison shown in Figure 3c clearly reveals that nearly all of the observed IR bands are also present in the LT condensate produced in the laboratory.…”
Section: Spectral Properties Of the Ht And Lt Condensatessupporting
confidence: 57%
“…When modelling the spectral energy distribution of IRC+10216, Ivezić & Elitzur (1996) derive a dust composition where MgS accounts for less than 10% by mass. For the carbon-rich post-AGB star HD 56126, Hony et al (2003) found that a MgS mass of ∼2% of the carbon dust mass is necessary to account for the 30 μm band flux. One would thus expect the MgS mass to represent at most a few percent of the AC dust mass in the inner wind of carbon stars.…”
Section: Mgs and Fesmentioning
confidence: 99%
“…While MgS has been proposed and often used as the carrier of this feature (Hony et al 2003), recent work has cast Grishko et al 2001;Hony et al 2003), should also be considered. In the SED model for PPN HD 56126, Hony et al (2003) showed that broad emission features around 7-9 μm and 10-13 μm are partly due to HACs, making the identification of the 30 μm band with HACs (Grishko et al 2001) a possibility. We examined whether HAC can be the main contributor to the 10-13 and 30 μm broad features by applying a modified blackbody model to the IRS spectrum, including both MgS and HACs.…”
Section: μM Broad Featurementioning
confidence: 99%
“…For MgS, we used the optical constants of nearly pure MgS, e.g., Mg 0.9 Fe 0.1 S, from Begemann et al (1994). For the HACs, we adopt the Q λ of HAC in the case of H/(H+C) = 0.3 calculated by Hony et al (2003). In two models, we consider different compositions, consisting of combinations of PAHs, amorphous carbon (AC), SiC, MgS, and HAC ( Figure 9).…”
Section: μM Broad Featurementioning
confidence: 99%